2016
DOI: 10.1681/asn.2015010074
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Renal Diseases

Abstract: Extracellular vesicles from the urine and circulation have gained significant interest as potential diagnostic biomarkers in renal diseases. Urinary extracellular vesicles contain proteins from all sections of the nephron, whereas most studied circulating extracellular vesicles are derived from platelets, immune cells, and the endothelium. In addition to their diagnostic role as markers of kidney and vascular damage, extracellular vesicles may have functional significance in renal health and disease by facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
175
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 125 publications
2
175
1
4
Order By: Relevance
“…In addition, extracellular vesicles including exosomes and microparticles (MPs) are emerging as novel vectors for cell–cell communication [12,13]. MPs are small plasma membrane-derived vesicles with a diameter of 100–1000 nm which carry a variety of proteins, lipids, mRNA and miRNA arising from the cell of origin [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, extracellular vesicles including exosomes and microparticles (MPs) are emerging as novel vectors for cell–cell communication [12,13]. MPs are small plasma membrane-derived vesicles with a diameter of 100–1000 nm which carry a variety of proteins, lipids, mRNA and miRNA arising from the cell of origin [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are a type of extracellular vesicles 30–100 nm in diameter that play a pivotal role in cell– cell communication [18]. Emerging studies have shown that exosomes act as key regulators of kidney injury [19]. Our previous studies have also found that transcriptomic changes in urinary exosomes can be utilized as discriminative biomarkers of mild renal fibrosis [20, 21], indicating their potential roles as the regulators and biomarkers of kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial that researchers provide detailed information about their methodology and use several techniques to ensure that the particles that they are studying are truly EVs and not non-EV components, such as lipids or protein complexes. In addition, a standard and uniform language should be used among all scientific communications [74].…”
Section: Microparticles In Kidney Transplantationmentioning
confidence: 99%